1996
DOI: 10.1002/hep.510240504
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of hepatitis B virus DNA polymerase by enantiomers of penciclovir triphosphate and metabolic basis for selective inhibition of HBV replication by penciclovir

Abstract: Chronic hepatitis B virus (HBV) infection has been esti-The deoxyguanosine analog penciclovir (PCV; 9-[4-mated to affect more than 300 million individuals worldwide, hydroxy-3-hydroxymethyl-but-1-yl]guanine), has shown and those affected are unable to benefit from recently develpotent antiviral activity against herpes viruses and hepoped hepatitis B surface antigen-containing vaccines. 1 Atadnaviruses. Efficacy against chronic hepatitis B virus tempts to control chronic HBV disease using antiviral chemo-(HBV) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
51
1

Year Published

1997
1997
2002
2002

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(54 citation statements)
references
References 38 publications
2
51
1
Order By: Relevance
“…6). Both specifically inhibit the hepadnaviral DNA polymerase/reverse transcriptase by competing with the corresponding dNTPs for incorporation into nascent DNA and acting as chain terminators after incorporation (11,33,35). Specific interference with the unique dGTP-dependent step which primes hepadnaviral reverse transcription (12) is an additional mechanism by which PCV exerts antihepadnaviral activity and which is not shared by 3TC.…”
Section: Discussionmentioning
confidence: 99%
“…6). Both specifically inhibit the hepadnaviral DNA polymerase/reverse transcriptase by competing with the corresponding dNTPs for incorporation into nascent DNA and acting as chain terminators after incorporation (11,33,35). Specific interference with the unique dGTP-dependent step which primes hepadnaviral reverse transcription (12) is an additional mechanism by which PCV exerts antihepadnaviral activity and which is not shared by 3TC.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that both the (R)-and (S)-enantiomers can inhibit HBV polymerase; however, the (R)-enantiomer was over 4-fold more potent than the (S)-enantiomer. 15,19 In our studies we used racemic PCVTP, which contains an equal proportion of both enantiomers.…”
Section: Discussionmentioning
confidence: 99%
“…15 Famciclovir was originally approved for the treatment of herpes simplex virus and herpes zoster virus. 16,17 Later, famciclovir was shown to have activity against human and duck hepatitis B viruses in enzymatic and cell culture assays and in animal models of infection.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 It was further shown that penciclovir triphosphate not only inhibits the DNA dependent DNA polymerase activity of the HBV polymerase, 5 but also the RNA-dependent activity of this enzyme, i.e., reverse transcription, by inhibiting the synthesis of the short DNA primer for reverse transcription. 6 Preliminary evidence suggested that famciclovir may have clinical utility in the treatment of chronic hepatitis B patients 7 and in orthotopic liver transplant patients.…”
mentioning
confidence: 99%